2014
DOI: 10.1038/nmat4134
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-ionic control of interfacial magnetism

Abstract: In metal/oxide heterostructures, rich chemical, electronic, magnetic and mechanical properties can emerge from interfacial chemistry and structure. The possibility to dynamically control interface characteristics with an electric field paves the way towards voltage control of these properties in solid-state devices. Here, we show that electrical switching of the interfacial oxidation state allows for voltage control of magnetic properties to an extent never before achieved through conventional magneto-electric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
544
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 488 publications
(574 citation statements)
references
References 35 publications
24
544
4
2
Order By: Relevance
“…In such systems, it has been shown that exchange interactions between spins of V 2+ and upper π * subband of TCNE lead to linear MR 64,65 . Thus electron-doped nickelates presents itself as a system with tunable magnetotransport mediated by ionic doping and could be of potential interest in the growing field of magneto-ionic devices 66 .…”
Section: Resultsmentioning
confidence: 99%
“…In such systems, it has been shown that exchange interactions between spins of V 2+ and upper π * subband of TCNE lead to linear MR 64,65 . Thus electron-doped nickelates presents itself as a system with tunable magnetotransport mediated by ionic doping and could be of potential interest in the growing field of magneto-ionic devices 66 .…”
Section: Resultsmentioning
confidence: 99%
“…The physical mechanisms of the purely electronic VCMA effect have been interpreted as the modification of the electronic structure at the interface through charge accumulation/depletion, [21][22][23] an electricfield-induced magnetic dipole 24 or the Rashba effect. 25 Chemical effects, such as a voltage-induced redox reaction, 26 or other electromigration 27 or charge trapping 28 effects can show a substantial VCMA coefficient of the order of a few thousands of fJ Vm − 1 , which is defined as the induced surface anisotropy energy change per unit electric field. However, these mechanisms have drawbacks of limited operational speed and writing endurance.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been published on electric-field-controlled magnetic effects in recent years, including magnetic domain wall propagation, 1-8 magnetic phase transitions, [9][10][11][12] spin polarization, 13,14 magnetic anisotropy [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and exchange bias. [33][34][35][36][37] Electric-field control of perpendicular magnetic anisotropy (PMA) would open up new prospects for the realization of high-density magnetic memory and logic technologies operating at low energy consumption levels.…”
Section: Introductionmentioning
confidence: 99%